Clinical and nutritional evaluation indicators of patients on waiting list for liver transplantation - Portugal, Milêda Lima Torres; Daltro, Ana Filomena Camacho Santos; Coêlho, Gustavo Rêgo; Batista, Bruna Aparecida Melo; de Oliveira, Ariclécio Cunha; de Almeida, Paulo César; Maia, Carla Soraya Costa (Revista da Associação Brasileira de Nutrição - RASBRAN, 2019)
Objective: Comparing different methods of clinical and anthropometric assessment of pre-liver transplant patients. Methods: This was a cross-sectional study with quantitative approach. We analyzed data from the medical records of pre-transplant patients older than 18 who received care at a Nutrition outpatient clinic of a Liver Transplant Center in Fortaleza-CE. We collected data regarding patient identification, clinical diagnosis, nutritional assessment and diagnosis. This study was approved by the Ethics Committee in Research of Walter Cantídio University Hospital of the Federal University of Ceará. Data were analyzed in the statistical program SPSSTM version 17.0 Results: The sample consisted of 71 patients, with 46 men (64.8%) and 25 women (35.2%), with a mean age of 53.7 years. The average BMI was 27.2 kg/m2; most women were healthy (60.0%) and most men were with excess of body weight (69.0%). As for the nutritional diagnosis according to the percentage of adequacy of the mid-upper arm circumference, we noted that 52.4% and 43.6% of female and male patients, respectively, showed some level of protein-calorie malnutrition. For the triceps skin fold, we noticed that most male patients (54.5%) were diagnosed as being overweight or obese. When assessing the percentage of adequacy of the mid-upper arm muscle area, most patients of both sexes had some level of malnutrition (62.3%). No significant correlation was observed between the MELD and Child-Pugh severity score (indices that encompass biochemical and clinical parameters for the prognostic evaluation of end-stage liver disease) and anthropometric variables. Conclusion: The severity indicators of the disease were not related to the anthropometric indices, but most patients who are eligible for a liver transplant were overweight according to BMI, although suffer from muscle mass depletion according to mid-upper arm muscle are, which shows the necessity of the combined use of several nutritional assessment methods in order to achieve a diagnosis of their body composition and, consequently, a faithful nutritional diagnosis.